2021
DOI: 10.1111/1462-2920.15681
|View full text |Cite
|
Sign up to set email alerts
|

Functional dissection of the phosphotransferase system provides insight into the prevalence of Faecalibacterium prausnitzii in the host intestinal environment

Abstract: Summary Faecalibacterium prausnitzii is a dominant member of healthy human colon microbiota, regarded as a beneficial gut bacterium due to its ability to produce anti‐inflammatory substances. However, little is known about how F. prausnitzii utilizes the nutrients present in the human gut, influencing its prevalence in the host intestinal environment. The phosphoenolpyruvate (PEP):carbohydrate phosphotransferase system (PTS) is a widely distributed and highly efficient carbohydrate transport system found in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 66 publications
1
19
0
Order By: Relevance
“…We confirmed that the putative PTS transporter was upregulated 35-fold in F. prausnitzii grown on inulin (Figure 6B). A BLAST search confirmed that this transporter responds specifically to fructose; a recent study has reported that a fructose-specific PTS transporter participates in the intracellular transport of fructose and is induced when F. prausnitzii is grown in the presence of fructose (Supplementary Table S7) (Kang et al, 2021). In addition, proteomic data confirmed that the transcriptional regulator and 1-phosphofructokinase encoded by the gene adjacent to the gene of the fructose PTS transporter were upregulated (Figure 6B).…”
Section: Upregulated Fructose Uptake Ability In F Prausnitzii Grown O...supporting
confidence: 62%
See 1 more Smart Citation
“…We confirmed that the putative PTS transporter was upregulated 35-fold in F. prausnitzii grown on inulin (Figure 6B). A BLAST search confirmed that this transporter responds specifically to fructose; a recent study has reported that a fructose-specific PTS transporter participates in the intracellular transport of fructose and is induced when F. prausnitzii is grown in the presence of fructose (Supplementary Table S7) (Kang et al, 2021). In addition, proteomic data confirmed that the transcriptional regulator and 1-phosphofructokinase encoded by the gene adjacent to the gene of the fructose PTS transporter were upregulated (Figure 6B).…”
Section: Upregulated Fructose Uptake Ability In F Prausnitzii Grown O...supporting
confidence: 62%
“…In addition, proteomic data confirmed that the transcriptional regulator and 1-phosphofructokinase encoded by the gene adjacent to the gene of the fructose PTS transporter were upregulated (Figure 6B). Because the PTS transporter transports sugar into the cell and simultaneously phosphorylates it, F. prausnitzii is expected to take up fructose into the cell through the fructose PTS transporter and phosphorylate it to fructose 1-phosphate, which is subsequently converted into fructose 1,6-bisphosphate by 1phosphofructokinase and enters the glycolytic pathway (Kang et al, 2021). To explore the activity of the fructose PTS transporter, we compared the growth ability of F. prausnitzii on glucose, fructose, sucrose, and inulin produced during the digestion process of inulin (Figure 7A).…”
Section: Upregulated Fructose Uptake Ability In F Prausnitzii Grown O...mentioning
confidence: 99%
“…(viii) Currently known targets of bacteriocins, such as the Man-PTS system used by several bacteriocins from different genera, to understand how a given system can be both a target to outcompete pathogens as seen in the review, and a mean for a commensal to better colonize a niche, as recently found for Faecalibacterium prausnitzi , one of the star bacteria from a healthy human colon. 275…”
Section: Current Standpoints To Future Directions: From Microbial Eco...mentioning
confidence: 99%
“…In agreement with previous studies in dairy calves ( 15 ), our results also observed a remarkable reduction in several inferred KEGG pathways associated with carbohydrate metabolism in the feces microbiome as weaned goats aged, conducive to the shift in nutrient metabolism. Given that the gut microbiota relies on the phosphotransferase system (PTS) to efficiently import cognate carbohydrates into cells ( 43 ), a drastic decrease in the PTS pathway was thus noted as goats aged. Considering that several pathways related to lipid and AA metabolism also changed with age, we can propose that gut bacteria can integrate their nutritional status with diverse environmental stimuli ( 15 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that the gut microbiota relies on the phosphotransferase system (PTS) to efficiently import cognate carbohydrates into cells ( 43 ), a drastic decrease in the PTS pathway was thus noted as goats aged. Considering that several pathways related to lipid and AA metabolism also changed with age, we can propose that gut bacteria can integrate their nutritional status with diverse environmental stimuli ( 15 , 43 ). Concurrently, it is further recapitulated that three pathways conducive to cell motility showed sequential progression in response to weaning.…”
Section: Discussionmentioning
confidence: 99%